Structure of Nests and Colony Sizes of the European Hornet (Vespa crabro) and Saxon wasp (Dolichovespula saxonica) (Hymenoptera: Vespinae) in Urban Conditions - Jerzy Nadolski (Sociobiology, 2014)
Studies of different groups of insects in urban areas sometimes show large populations, greater than in non-urban areas. The reason for this is a presence in the cities some of dominating species which often occur almost en masse. This group includes, inter alia, hymenopterans and especially social wasps (Vespinae). Colonies and nests of two wasp species, the European hornet (Vespa crabro) and Saxon wasp (Dolichovespula saxonica) in areas of the city of Łódź in Poland were studied. Whole colonies positioned both in buildings as well in natural places, size of societies, parameters their nests, differentiation of cells in combs and their location were investigated. We also studied the correlation between the size of the nest and societies of these insects. It was found that nests established in the buildings are much larger, produced more individuals of reproductive castes and thus obtained a better reproductive success especially for the hornet colonies whose queens prefer the buildings as a place to nest.